Physical exercise and covid-19 - Balan, Lucas Esperidião; Youssef, Felipe; Santos, Fernando Pereira dos (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 39 No 76 (2023): Publicação Contínua, 2023)
The coronavirus pandemic has impacted several areas, including the population's quality of life. This review will seek to relate some physiological effects provided by physical exercise that contribute to the containment of COVID-19, and it is important to highlight that it is not necessary to be in a gym to practice regular exercise.